2019
DOI: 10.1016/s1474-4422(19)30185-1
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and the trigeminovascular system—40 years and counting

Abstract: The underlying causes of migraine headache remained enigmatic for most of the 20th century. In 1979, The Lancet published a novel hypothesis proposing an integral role for the neuropeptidecontaining trigeminal nerve. This hypothesis led to a transformation in the migraine field and understanding of key concepts surrounding migraine, including the role of neuropeptides and their release from meningeal trigeminal nerve endings in the mechanism of migraine, blockade of neuropeptide release by anti-migraine drugs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
299
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 379 publications
(312 citation statements)
references
References 91 publications
4
299
0
9
Order By: Relevance
“…Advances in therapies have made it possible to effectively prevent or reduce symptoms of migraine. Humanized monoclonal antibodies targeting CGRP and its receptor have recently been approved for migraine prophylaxis in adults [75,79,91,101,127,128]. Fremanezumab, a monoclonal antibody specific to CGRP, was approved by the FDA in September 2018 and by the EMA in March 2019 for migraine prevention in adults [76,90].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in therapies have made it possible to effectively prevent or reduce symptoms of migraine. Humanized monoclonal antibodies targeting CGRP and its receptor have recently been approved for migraine prophylaxis in adults [75,79,91,101,127,128]. Fremanezumab, a monoclonal antibody specific to CGRP, was approved by the FDA in September 2018 and by the EMA in March 2019 for migraine prevention in adults [76,90].…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that monoclonal antibodies act peripherally because they do not cross the blood-brain barrier [79,87]. Possible sites of action for fremanezumab are the trigeminal ganglion and meningeal nociceptors [78,87,101]. A study in rats found that fremanezumab selectively inhibits activation of peripheral lightly myelinated Ad (but not unmyelinated C) meningeal neurons and central high-threshold (HT) [but not wide-dynamic-range (WDR)] trigeminovascular neurons by cortical spreading depression (CSD) in the meningeal sensory pathway [78,87].…”
Section: Cgrp As a Target: Mechanism Of Actionmentioning
confidence: 99%
“…The trigeminovascular system plays an integral role in migraine pathogenesis 11 . Within this framework, CGRP and various other neuropeptides are heavily involved in mediating certain aspects of the headache phase of migraine 12,13 .…”
Section: Cgrp and Migrainementioning
confidence: 99%
“…There are potential pathophysiological overlaps with migraine and neuroendocrineimmune-related skin disorders, in which also calcitonin gene related peptide (CGRP) has been suggested to play a role. Moreover, the role of vascular changes in rosacea and migraine are not fully understood but remain an interesting hypothesis also when reflecting on genetic studies [21,38,39].…”
Section: Increased Comorbidity Based On Phenotypic Disease Networkmentioning
confidence: 99%